Pengaruh Harga Diri Terhadap Kecanduan Media Sosial pada Siswa SMA - Andanu, Dery (Neolectura, 2024)
This study aims to examine the influence of self-esteem on social media addiction among high school students. The research employs a quantitative methodology and utilizes snowball sampling, targeting respondents who are high school students aged 15-18 years and use social media for more than 6 hours a day. The sample size for this study is 128 respondents. Data on self-esteem is measured using a self-esteem scale, while social media addiction is measured using a social media addiction scale. The data analysis technique used is simple regression analysis. The results of the analysis indicate that the hypothesis is supported, showing an influence of self-esteem on social media addiction among high school students, with a significance value of 0.000 (p < 0.01) and an R Square value of 0.137. This means that self-esteem accounts for 13.7% of the influence on social media addiction, while 86.3% is influenced by other factors.